Emerging roles for stress kinase p38 and stress hormone fibroblast growth factor 21 in NAFLD development - Junli Liu (Elsevier, 2021)
Non-alcoholic fatty liver disease (NAFLD), the most frequent cause of chronic liver disease worldwide, is associated with a plethora of metabolic comorbidities such as obesity, prediabetes, type 2 diabetes mellitus, hypertension and dyslipidemia but may be present in a significant percentage of non-obese subjects. Recent evidence has highlighted that NAFLD is characterized by the dysregulation of hepatokines, including fibroblast growth factor 21 (FGF21). “FGF21 resistance” observed in obesity and NAFLD is actually not fully understood. A very recent study by Hao Ying et al. in Diabetes provides new insight into the roles of hepatic stress kinase p38 and FGF21 in the pathogenesis of NAFLD. This study has shown that mechanistically, via the elevation of hepatic FGF21, p38α activation increases the influx of fatty acids from the adipose tissue to liver, resulting in hepatic ectopic lipid accumulation and insulin resistance. Despite the favorable effects of p38α activation on peripheral tissues, it may impair the hepatic FGF21 properties by enhancing the degradation of FGF21 receptor cofactor β-Klotho. Ιn the fatty liver of either mice or patients, the study has shown that p38α phosphorylation and FGF21 expression were elevated while β-Klotho protein levels were diminished. Based on the observation that mice with hepatic p38α activation exhibit not only hepatic steatosis but also reduced adiposity, which is similar to those observed in lean NAFLD, these findings may also provide a plausible explanation for the lean phenotype seen in NAFLD. In conclusion, this study highlighted previously undescribed effects of hepatic p38 activation on systemic metabolic homeostasis providing novel insights into the contribution of hepatic p38α, FGF21, and β-Klotho in the etiopathogenesis of NAFLD.